COUNSELING OF FAMILY FINANCIAL MANAGEMENT LITERACY PROGRAM KELUARGA HARAPAN BENEFICIARIES - Sabinus BENI (Pusat Pengabdian kepada Masyarakat- LPPM Universitas Terbuka, 2019)
Community service was carried out in Setia Budi Village, Bengkayang District, West Kalimantan. The event was held on February 18, 2019 with 97 participants as Pre-Prosperous Family beneficiaries of the Hope Family Program. The purpose of this activity is that the families of the beneficiaries of the family program hope to manage their wealth well so that the assistance in the form of cash received is right on target and managed well. The method used in the form of lectures and question and answer and the practice of directly preparing the family financial budget. The results expected in this activity are to assist the government in managing family finances so that beneficiary families can graduate independently from their participation as beneficiaries of family program expectations because economy has increased.